Unraveling the Pathogenesis of MDS: The NLRP3 Inflammasome and Pyroptosis Drive the MDS Phenotype - Sallman, David A.; Cluzeau, Thomas; Basiorka, Ashley A.; List, Alan (Frontiers in Oncology, 2016)
Myelodysplastic syndromes (MDS) are characterized by bone marrow cytological dysplasia and ineffective hematopoiesis in the setting of recurrent somatic gene mutations and chromosomal abnormalities. The underlying pathogenic mechanisms that drive a common clinical phenotype from a diverse array of genetic abnormalities has only recently begun to emerge. Accumulating evidence has highlighted the integral role of the innate immune system upregulating inflammatory cytokines via NF-ᴋB activation in the pathogenesis of MDS. Recent investigations implicate activation of the NLRP3 inflammasome in hematopoietic stem/progenitor cells (HSPCs) as a critical convergence signal in MDS with consequent clonal expansion and pyroptotic cell death though caspase-1 maturation. Specifically, the alarmin S100A9 and/or founder gene mutations trigger pyroptosis through generation of reactive oxygen species leading to assembly and activation of the redox-sensitive NLRP3 inflammasome and β–catenin, assuring propagation of the MDS clone. More importantly, targeted inhibition or varied steps in this pathway restores effective hematopoiesis. Together, delineation of the role of pyroptosis in the clinical phenotype of MDS patients has identified novel therapeutic strategies that offer significant promise in the treatment of MDS.